The Digitalization Paradox: Assessing Policy Implementation, Organizational Misalignment, and User Dissatisfaction in Indonesia's National Sports Information System - Muhammad Raditya Saputra; Triyuni Soemartono; Budiharjo Budiharjo; Dedeh Maryani (Danadyaksa: Post Modern Economy Journal, 2026)
Indonesia's National Sports Grand Design (the Desain Besar Olahraga Nasional - DBON) positions digitalization as its core governance instrument, operationalized through the mandated Sports Personnel and Organization Information System (the Sistem Informasi Tenaga dan Organisasi Keolahragaan, SITENOR). However, implementing centralized digital policies in complex, multi-stakeholder environments often creates a significant gap between strategic vision and ground-level reality. This study evaluates the effectiveness of this digitalization policy by examining SITENOR’s implementation. Employing a qualitative interpretivist paradigm, this research conducted in-depth interviews and Focus Group Discussions (FGDs) with key policymakers from the Ministry of Youth and Sports (Kemenpora), system developers, and representatives from national sports federations. Data were analyzed using the integrated lenses of the McKinsey 7S organizational framework and the End-User Computing Satisfaction model. The findings reveal a profound "digitalization paradox." While the central strategy and technical system (the "hard" elements) are well-defined, implementation is critically undermined by weaknesses in "soft" organizational elements: a misalignment of shared values (compliance vs. data-driven culture), passive local leadership, a severe deficit in dedicated staff and digital skills, and consequent low user satisfaction regarding data accuracy, ease of use, and timeliness. SITENOR’s development is assessed as stalled at an incomplete cataloguing and transactional stage, with minimal vertical and horizontal integration. The effectiveness of the DBON digitalization policy is significantly constrained not by technology but by socio-organizational and governance gaps. Successful transformation requires a strategic pivot from a top-down, compliance-based model to a co-creative, capacity-sensitive approach that builds human infrastructure and fosters genuine data-driven values across the sports ecosystem.